(3EWdGdI eYQajI Ydi THcGJ GdJhGUd GdGLJeGYj (B: s (3GdajSHhc, GdJhjJQ, GdjhJjhH (B/ s - (3efUhQj, NGdO NdaGf CMeO(B.s ((3OHj (B: s (3eQcR GdHMhK h GdOQGSGJ HCcGOjejI TQWI OHj, s, 2013)
(3fXQG dJYGXe OhQ ehGbY GdJhGUd GdGLJeGYj aj GdYGde GdYQHj, MjK JLGhR YOO eSJNOej gPg GdehGbY aj YGe (B2011 (3MhGdj (B21,3 (3edjhf eSJNOe(B. (3hLOjQ HGdPcQ Cf OhdI GdEeGQGJ GdYQHjI GdeJMOI JYO GdChdi YQHjkG ef MjK GSJNOGe ehGbY GdJhGUd, MjK hUd YOO eSJNOej ehbY GdajSHhc aj OhdI GdEeGQGJ Edi fSHI (B44.57%(3, Cj MhGdj (B2.9 (3edjhf eSJNOe eY HOGjI GdYGe GdLGQj(B. (3dgPG bGe eQcR GdHMhK hGdOQGSGJ HYed OQGSI cEWdGdI eYQajI HgOa fTQ GdKbGaI GdYGeI ef MjK JSdjW GdVhA Ydi GdJYQja HTHcGJ GdJhGUd GdGLJeGYj hHjGf TQhW GSJNOGegG hYQV Cge eejRGJgG heNGWQgG, HGdEVGaI Edi YQV MbGFb aj SjGSI GdNUhUjI hMeGjI GdHjGfGJ aj GdYGde GdQbej(B.s
Keywords: (3ehGbY GdJhGUd GdGLJeGYj(B. s; (3GdTHcGJ GdGLJeGYjI(B.s; (3GdEYdGe s -- (3GdLhGfH GdGLJeGYjI(B. s; (3LQGFe GdMGSHGJ GdEdcJQhfjI(B.s